Evaluation of contamination of equipment, utensils, and hands of food handlers of a Hospital Nutrition and Dietetics Service - dos Santos, Amanda de Oliveira [UNESP]; Sampaio, Aryele Nunes da Cruz Encide [UNESP]; Martins, Otávio Augusto [UNESP]; de Almeida Nogueira Pinto, José Paes [UNESP]; Pereira, Juliano Gonçalves [UNESP] (Universidade Federal do Paraná, 2020)
The Nutrition and Dietetics Service (NDS) is the sector of a hospital responsible for developing activities related to food and nutrition for patients, companions and employees. Care for food safety in the hospital environment is of fundamental importance, since the food prepared in this location will be directed, in most cases, to immunocompromised patients. The objective of the present study was to evaluate the hygienic-sanitary conditions of surfaces, equipment, utensils and hands of food handlers of an NDS of a public hospital in the Midwest of the State of Sao Paulo. By means of a superficial swab, samples were collected from 101 surfaces, equipment and utensils and from 46 hands of food handlers. The samples were subjected to counts of mesophilic, coliform and Escherichia coli and the positive coagulase Staphylococcus count was also performed in the hands of food handlers. It was observed that 51.4% of the surfaces, equipment, utensils and surfaces were out of the standard for mesophiles, 50.4% for coliforms and 3.9% for E. coli. Of the 46 sampled hands, 23.9% showed non-standard results for mesophiles, 32.6% for coliforms and only 2.1% for E. coli and coagulase positive Staphylococcus. The results showed errors in the process of cleaning surfaces, equipment, utensils and hands, which can directly influence the quality and safety of the food offered to patients, companions and collaborators.
Avaliação da contaminação de equipamentos, utensílios e mãos de Manipuladores de um Serviço de Nutrição e Dietética
Keywords: Health; Hospital nutrition; Microorganisms